Reduksi Faktor-Faktor yang Mempengaruhi Kualitas Air Hujan dengan Metode Analisis Komponen Utama - Nitasari, Alfi Nur; Salsabila, Fatiha Nadia; Ramadhanty, Devira Thania; Anggriawan, Muhammad Rizal; Amelia, Dita; Mardianto, M. Fariz Fadillah; Ana, Elly (Zeta - Math Journal, 2023)
The increase in air pollution that occurs due to industrial and economic activities will affect the rainwater content. The vital function of one of the sources of clean, namely rainwater, makes the urgency of research on indications of a decrease in rainwater quality by analyzing the substances contained. The parameters used for the determination of rainwater quality are the degree of acidity, conductivity, calcium, magnesium, sodium, potassium, ammonium, sulfate ions, nitrate ions, chloride ions, total hardness, and acidity. The data source used is data from the Central Statistics Agency (BPS) entitled "Indonesian Environmental Statistics 2022". By using the main component analysis method to reduce the variables of rainwater quality influence factors in 35 city/station samples in Indonesia, results were obtained, namely rainwater quality influence factors that can be formed into three main components with each containing 10 variables consisting of acidity, conductivity, magnesium, sodium, potassium, chloride ions, sulfate ions, nitrate ions, total hardness, and acidity capable of explaining 73.695% of the total variance.